OPOSISI DALAM KEHIDUPAN DEMOKRASI: ARTI PENTING KEBERADAAN OPOSISI SEBAGAI BAGIAN PENGUATAN DEMOKRASI DI INDONESIA - Noor, Firman (Masyarakat Indonesia, 2018)
In real politics, the acknowledgement and implementation of democracy would be in vain if the government in daily basis is actually run without any effective controls or balancer from the opposition. Such a government is actually close to the oligarchy or authoritarian government. Indonesia as a country that believes in democracy up until today still has not been able to develop a strong opposition. In this regards, this article aims to discuss the relationship between democracy and opposition. Some specific issues would also be discussed namely, (1) the essence of opposition in democratic framework, (2) the opposition in Indonesian politics and why it is important for democracy strengthening, (3) some aspects that should be performed in order to solidify opposition in political life.